Improving domestic enforcement of socio-economic rights through international law : ratification of the International Covenant on Economic, Social and Cultural Rights by South Africa - Chenwi, Lilian (University of Pretoria, 2010)
A dissertation submitted to the Faculty of Law University of Pretoria, in partial fulfilment of the requirements for the degree Masters of Law (LLM in Human Rights and Democratisation in Africa). Prepared under the supervision of Dr Lilian Chenwi, Faculty of law, University of Western Cape, South Africa.